Transfer of Technology through Krishi Vigyan Kendra for the Tribal Farmers in Hilly Areas of Koraput District - BEHERA, S. K.; MAHARANA, J. R.; ACHARYA, P. (Indian Journal of Hill Farming, 2015)
The Krishi Vigyan Kendras (KVK) is of national importance which would help in accelerating the agricultural production and also in improving the socio-economic conditions of the farming community. Krishi Vigyan Kendra, Koraput is situated in the Eastern Ghat Highland Agro-climatic Zone of Orissa to cater the needs of the farming communities of Koraput district. Need based training programmmes are being conducted by the KVK in various disciplines such as agronomy, horticulture, soil science, women in agriculture, agricultural engineering and others. Survey method by personal interview was used for collecting the required information on component wise crop production technology transferred, extent of adoption of technology, discipline wise training organized by KVK and farmers response towards training, costs and returns of crop production. It was concluded that KVK, Koraput playing a vital role in disseminating the improved crop production technology and helps in increasing the crop yield. Further research need to be focused on the problems and constraint for adoption of the technology.